Setting Emission Reduction Trajectories in Mediterranean Cities with the Use of Science-Based Targets: The Pathway towards Climate Neutrality and the Ambitious European Goals by 2050 - Eleni Feleki; Nicolas Moussiopoulos (Atmosphere, 2021)
Mediterranean cities, having already suffered from climate change and at risk of being further affected if actions are not taken, need to reduce their emissions and set themselves on a path towards achieving the Paris Agreement ambition of limiting global warming to 1.5 °C. There are several methodologies that have been developed recently for cities in order to set a science-based target in line with a 1.5 °C scenario, that can be adopted by Mediterranean cities. In this short communication, we have selected to refer to two of them with the aim of inspiring experts from Mediterranean cities and providing relevant tools and further learning resources in order to make this task achievable. The new framework is guiding cities towards a greener and more sustainable transition. With a concrete framework to limit greenhouse gas emissions, the Mediterranean Basin can follow the global push to net-zero emissions by mid-century.